Post-therapeutic support and rehabilitation for breast cancer women in complete remission in a thermal resort: study protocol for the PACThe Real-Life conditions observational trial - Mélanie Godiveau; Judith Passildas; Emilie Thivat; Mélanie Casile; Céleste Pinard; Alexia Giro; Marie-Ange Mouret-Reynier; Ioana Molnar; Catherine Abrial; Claude-Eugène Bouvier; Yves-Jean Bignon; Xavier Durando (BMC Cancer)
Abstract Background Over the past twenty years, the post-cancer rehabilitation has been developed, usually in a hospital setting. Although this allows better care organization and improved security, it is perceived as stressful and restrictive by the “cancer survivor”. Therefore, the transfer of benefits to everyday life is more difficult, or even uncertain. Staying in a thermal resort seemed to offer a good compromise: the security and structure of centralized reception in a thermal resort for treatment and medical supervision, and accommodation in a hotel with full dietary board. It combines institutional quality and security with the freedom of real life and the dynamics of a group formed under innovative conditions. This rehabilitation procedure was tested with the program PACThe (Program of Accompanying women after breast Cancer treatment completion in Thermal resorts) which was evaluated at one year in a randomized controlled trial involving 251 patients [1] and at five years in another study [2]. The results shown a significative improvement in many areas such as quality of life, functional abilities and sleep. The aim of this study is therefore to confirm the benefits of the PACThe program at six months for breast cancer women in complete remission in real-life conditions. Methods The project PACThe Real-Life conditions is an observational trial in which 400 breast cancer women in complete remission will be sent to a 3 week thermal “post-cancer rehabilitation” program. Primary objective is to assess the quality of life until 12 months. The outcome will be measured with the self-questionnaire SF-36 [3] at five timepoints (inclusion visit, end of thermal resort, 6 months post-cure, 12 months post-cure and 18 months post-cure). The duration of patient participation in the study will therefore be 18 months. The main analysis will consist of comparing the SF-36 global score at 6 months with the baseline. Discussion This study aims to investigate the improvements in quality of life of 3 weeks stay at thermal resort for breast cancer women in complete remission. The comprehensive overview of the program PACThe will likely contribute to enhancing thermal therapy post-cancer rehabilitation in this population in real life conditions. Trial registration The PACThe Real-Life conditions trial is a prospective observational study registered at the ANSM registry (2022-A00171-42) on March 1, 2022. This study has been registered on ClinicalTrials.gov: NCT05433077. Protocol: version 4, 22 December 2022.